Comment on 'ShangS. 2012. Calculating actual crop evapotranspiration under soil water stress conditions with appropriate numerical methods and time step. Hydrological Processes26: 3338–3343. DOI: 10.1002/hyp.8405'. Issue 11 (9th February 2014) - Yatheendradas, Soni; Narapusetty, Balachandrudu; Peters‐Lidard, Christa; Funk, Christopher; Verdin, James
Abstract A previous study analyzed errors in the numerical calculation of actual crop evapotranspiration (ETa) under soil water stress. Assuming no irrigation or precipitation, it constructed equations for ETa over limited soil‐water ranges in a root zone drying out due to evapotranspiration. It then used a single crop‐soil composite to provide recommendations about the appropriate usage of numerical methods under different values of the time step and the maximum crop evapotranspiration (ETc). This comment reformulates those ETa equations for applicability over the full range of soil water values, revealing a dependence of the relative error in numerical ETa on the initial soil water that was not seen in the previous study. It is shown that the recommendations based on a single crop‐soil composite can be invalid for other crop‐soil composites. Finally, a consideration of the numerical error in the time‐cumulative value of ETa is discussed besides the existing consideration of that error over individual time steps as done in the previous study. This cumulative ETa is more relevant to the final crop yield. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.